Pazopanib for Metastatic Renal Cell Carcinoma: A Registry-based Analysis of 426 Patients - Poprach, Alexandr; Fiala, Ondrej; Chloupková, Renata; Melichar, Bohuslav; Lakomy, Radek; Petrakova, Katarina; Zemanova, Milada; Kopeckova, Katerina; Slaby, Ondrej; Studentova, Hana; Kopecký, Jindrich; Kiss, Igor; et al. (Anticancer research, 2018)
BACKGROUND: Pazopanib is approved for the first-line treatment of patients with metastatic renal cell carcinoma (mRCC). The present study was a retrospective registry-based analysis of 426 patients with mRCC treated with pazopanib as first-line targeted therapy. PATIENTS AND METHODS: The data were obtained from the Renal Cell Carcinoma Information system registry. Patient baseline parameters, treatment course and outcomes, and toxicity were analysed. RESULTS: Median progression-free and overall survival were 12.9 (95% confidence interval(CI)=11.0-14.8) months and 33.2 (95% CI=29.9-36.4) months, respectively. Overall response rate and disease control rate were 25.1% and 57.4%, respectively. Adverse events led to discontinuation of treatment in 37 (12.1%) patients. CONCLUSION: The results confirm that pazopanib is an effective and safe first-line targeted treatment in patients with mRCC. Both the International mRCC Database Consortium and the Memorial Sloan Kettering models were valid predictors of prognosis and nephrectomy was associated with improved survival.
Keywords: dospělí; Indoles; receptory růstového faktoru odvozeného z trombocytů; Female; indoly; pyrimidiny; Adult; výsledek terapie; ženské pohlaví; přežití bez známek nemoci; Receptors, Platelet-Derived Growth Factor; Registries; lidé; Angiogenesis Inhibitors; inhibitory angiogeneze; Sulfonamides; karcinom z renálních buněk; databáze faktografické; receptory vaskulárního endoteliálního růstového faktoru; Treatment Outcome; Aged, 80 and over; Nephrectomy; Kidney Neoplasms; Carcinoma, Renal Cell; Receptors, Vascular Endothelial Growth Factor; retrospektivní studie; protoonkogenní proteiny c-kit; Male; Aged; Czech Republic; sulfonamidy; Pyrroles; Proto-Oncogene Proteins c-kit; Česká republika; nádory ledvin; Databases, Factual; Disease-Free Survival; lidé středního věku; registrace; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; pyrroly; Middle Aged; nefrektomie; Pyrimidines; Humans